2020
DOI: 10.7200/esicm.168.0521.1
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of wellbeing in the effect of human resources management on performance

Abstract: Aims:The objective of this study is to build a scale of the wellbeing of teachers in education centres. In addition, it examines the incidence of human resources management on educational performance, both directly and through the mediating effect of the wellbeing of teachers in terms of both the psychological and the physical. Methodology: The study uses the methodology of structural equations, and a sample of 315 questionnaires for teachers working in secondary education. Results: This study corroborates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results of the present study revealed that the impact of HCHRM practices on POS and job satisfaction was significant, corroborating the findings of several studies that highlight the positive effects of HR practices on employee well-being (e.g. (Salas-Vallina et al , 2021); Pagán Castaño et al , 2020). Moreover, Hameli and Bela (2023) conducted an investigation on the effects of HCHRM practices on psychological conditions and found a significant positive impact of HCHRM practices on psychological conditions, playing a crucial mediating role in the relationship between HCHRM practices and overall employee well-being.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study revealed that the impact of HCHRM practices on POS and job satisfaction was significant, corroborating the findings of several studies that highlight the positive effects of HR practices on employee well-being (e.g. (Salas-Vallina et al , 2021); Pagán Castaño et al , 2020). Moreover, Hameli and Bela (2023) conducted an investigation on the effects of HCHRM practices on psychological conditions and found a significant positive impact of HCHRM practices on psychological conditions, playing a crucial mediating role in the relationship between HCHRM practices and overall employee well-being.…”
Section: Discussionsupporting
confidence: 90%